Why are we talking about Norway? Discourses of Norway's exceptionality in global media coverage of electric vehicles - Ville Kumpu (Social Sciences and Humanities Open)
This article sheds light on the discursive context within which road transport electrification is negotiated and enacted around the world by examining how Norway's exceptionality is constructed in media coverage of electric vehicles (EV). Wherever road transport electrification is debated, Norway is likely to be mentioned as a case in point. The exceptionality of Norway may be framed in many ways, which reflect different ideas of why and how road transport electrification is taking place as a global change. As a part of the global discursive context, the construction of Norway's exceptionality shapes how road transport electrification is deliberated at the national level. The discourse analysis presented in this article shows that there were five discourses involved in the construction of Norway's exceptionality. It was typically constructed with the purpose of either comparing or ranking countries for their EV adoption. Norway was also referred to with the purpose of illustrating change, asking critical questions, and empowering learning. The findings of this study indicate that road transport electrification is not understood as a global challenge requiring countries to work together, but as a transition that countries are enacting individually in a context of constant mutual comparison and competition.